GRK5 Inhibition Attenuates Cartilage Degradation via Decreased NF‐κB Signaling. Issue 4 (5th March 2020) - Sueishi, Takuya; Akasaki, Yukio; Goto, Norio; Kurakazu, Ichiro; Toya, Masakazu; Kuwahara, Masanari; Uchida, Taisuke; Hayashida, Mitsumasa; Tsushima, Hidetoshi; Bekki, Hirofumi; Lotz, Martin K.; Nakashima, Yasuharu
Abstract : Objective: NF‐κB–dependent signaling is an important modulator in osteoarthritis (OA), and G protein–coupled receptor kinase 5 (GRK5) regulates the NF‐κB pathway. This study was undertaken to investigate the functional involvement of GRK5 in OA pathogenesis. Methods: GRK5 expression in normal and OA human knee joints was analyzed immunohistochemically. Gain‐ or loss‐of‐function experiments were performed using human and mouse chondrocytes. OA was induced in GRK5‐knockout mice by destabilization of the medial meniscus, and histologic examination was performed. OA was also induced in wild‐type mice, which were then treated with an intraarticular injection of amlexanox, a selective GRK5 inhibitor, every 5 days for 8 weeks. Results: GRK5 protein expression was increased in human OA cartilage. In vitro, expression levels of OA‐related factors and NF‐κB transcriptional activation were down‐regulated by suppression of the GRK5 gene in human OA chondrocytes (3.49‐fold decrease in IL6 [ P < 0.01], 2.43‐fold decrease in MMP13 [ P < 0.01], and 2.66‐fold decrease in ADAMTS4 [ P < 0.01]). Conversely, GRK5 overexpression significantly increased the expression of OA‐related catabolic mediators and NF‐κB transcriptional activation. On Western blot analysis, GRK5 deletion reduced IκBα phosphorylation (up to 4.4‐fold decrease [ P < 0.05]) and decreased p65 nuclear translocation (up to 6.4‐fold decrease [ P < 0.01]) in mouse chondrocytes. In vivo, both GRK5 deletion and intraarticular amlexanox protected mouse cartilage against OA. Conclusion: Our results suggest that GRK5 regulates cartilage degradation through a catabolic response mediated by NF‐κB signaling, and is a potential target for OA treatment. Furthermore, amlexanox may be a major compound in relevant drugs.